DESAIN REAKTOR UNTUK PRODUKSI NANOPRATIKEL PERAK DALAM MEDIA POLIMER ALAMI - Tria Nurwina Novianti; Asep Bayu Dani Nandiyanto; Risti Ragadhita (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2023)
The aim of this research is to design a reactor for the production of silver nanoparticles in natural polymeric media. The method used is to perform computational analysis to obtain a reactor design with specifications for a total reactor volume of 304.865 ft3, vessel diameter of 73.29 in, cylinder liquid volume of 92.87 in, design pressure of 18.97 psia, cylinder thickness of 73.44 in, height cylinder 10.77 ft, lid dimension 12.38 in, and lid dimension 21.18 in. These results are obtained according to calculations assuming the input mass is enlarged 100x from the reference journal used. This research can be used as a standard for making reactors to produce silver nanoparticles in natural polymeric media.